2021
DOI: 10.1007/s11575-021-00439-w
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Decision Speed and International Performance: The Roles of Competitive Intensity, Resource Flexibility, and Structural Organicity

Abstract: Based on insights from the decision-making and contingency theories, this study examined the influence of strategic decision speed (SDS) on the international performance of small and medium-sized enterprises (SMEs), and explored the conditions under which SDS effectively drives international performance. We tested our model using structural equation modeling using a sample of 212 SMEs involved in crossborder activities. First, the results show that fast decision-making is associated with greater international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 112 publications
(167 reference statements)
0
23
0
Order By: Relevance
“…Second, the present study extends our knowledge on the boundary conditions of the impacts of R&D support on technological capability. Although the role of R&D support on technological capability has been examined (Adomako, Frimpong, Amankwah‐Amoah, et al, 2021a; Kang, Baek, & Lee, 2017), the conditions under which the use of R&D support drives technological capability remain elusive. It can be concluded that this study is the first to examine technological turbulence, a moderating variable on this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the present study extends our knowledge on the boundary conditions of the impacts of R&D support on technological capability. Although the role of R&D support on technological capability has been examined (Adomako, Frimpong, Amankwah‐Amoah, et al, 2021a; Kang, Baek, & Lee, 2017), the conditions under which the use of R&D support drives technological capability remain elusive. It can be concluded that this study is the first to examine technological turbulence, a moderating variable on this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SMEs in Ghana have attained some of the trappings of internationalization, specifically their presence in the Economic Community of West Africa States (ECOWAS) sub‐region. Therefore, using SMEs from Ghana to test our hypotheses will help us to contribute to the IB literature by examining how and when firms could leverage the effects of R&D support in their internationalization drive (Adomako et al, 2021b; Adomako, Amankwah‐Amoah, Tarba, & Khan, 2021c; Adomako, Frimpong, Amankwah‐Amoah, Donbesuur, & Opoku, 2021a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of competitive rivalry, (1) firms are engaged in continuous and quick introduction of innovative products with an intention to outperform competitors and acquire market share (Bachmann, Ohlies, and Flatten 2021); (2) price, promotion, and other wars are more likely to erupt among rival firms in an effort to gain market share (Ndubisi et al 2020); and (3) customers have greater information about alternative market offerings, increasing in this way the possibility to switch among competitors (Adjei, Griffith, and Noble 2009). These conditions necessitate specific actions by SMEs, such as making quick and proactive movements (Adomako et al 2021), becoming more responsive to competitors’ actions and market needs (Gaur, Vasudevan, and Gaur 2011), and taking riskier initiatives to improve differentiation from the competition (Abebe and Angriawan 2014).…”
Section: Background Researchmentioning
confidence: 99%
“…Among the subtypes described in the literature, two kinds of flexibility are in line with the aims of this study. The first concerns resource flexibility , dealing with the ability to dynamically reallocate resources while strengthening them [ 12 ]. This study highlights the internal dimension of hospitals to explain their capacity to effectively manage two competing sets of needs.…”
Section: Introductionmentioning
confidence: 99%